2002
DOI: 10.1042/bj20020973
|View full text |Cite
|
Sign up to set email alerts
|

Identification of in vitro and in vivo phosphorylation sites in the catalytic subunit of the DNA-dependent protein kinase

Abstract: The DNA-dependent protein kinase (DNA-PK) is required for the repair of DNA double-strand breaks (DSBs), such as those caused by ionizing radiation and other DNA-damaging agents. DNA-PK is composed of a large catalytic subunit (DNA-PKcs) and a heterodimer of Ku70 and Ku80 that assemble on the ends of double-stranded DNA to form an active serine/threonine protein kinase complex. Despite in vitro and in vivo evidence to support an essential role for the protein kinase activity of DNA-PK in the repair of DNA DSBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 43 publications
8
169
1
Order By: Relevance
“…Previously, it has been suggested that autophosphorylation at more than one site is likely to be required for DNA-PKcs function in NHEJ in vivo . Phosphorylation of DNA-PKcs at S2056 as well as at T2609 has been shown to occur in vivo in response to DNA damage (Chan et al, 2002;Douglas et al, 2002). Compelling evidence based on location, model systems and response to various DNA-damaging agents indicates that these amino-acid residues may be distinctly regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been suggested that autophosphorylation at more than one site is likely to be required for DNA-PKcs function in NHEJ in vivo . Phosphorylation of DNA-PKcs at S2056 as well as at T2609 has been shown to occur in vivo in response to DNA damage (Chan et al, 2002;Douglas et al, 2002). Compelling evidence based on location, model systems and response to various DNA-damaging agents indicates that these amino-acid residues may be distinctly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of DNA-PK activity is not exclusively regulated by the coordinated assembly of Ku and DNA-PKcs on DNA ends. In this respect, it has been reported that DNA-PKcs can undergo autophosphorylation (Chan et al, 2002;Douglas et al, 2002Douglas et al, , 2007Chen et al, 2005). To date, it is not clear which is the exact role of this event, although some studies have reported that autophosphorylation of purified DNAPKcs results in disruption of the DNA-PK complex in vitro and loss of kinase activity in vivo (Chan and Lees-Miller, 1996;Merkle et al, 2002;Ding et al, 2003;Block et al, 2004;Douglas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…8 Subsequently, the Artemis protein is phosphorylated by DNA-PKcs and opens the hairpinsealed coding ends. 9,10 The coding ends are then further processed by inclusion of palindromic (P) nucleotides due to asymmetric hairpin opening, loss of nucleotides due to exonuclease activity and addition of nontemplated (N) nucleotides by terminal deoxynucleotidyl transferase. 11 In the final step, the coding ends are ligated by the DNA ligase IV (LIG4)/XRCC4 complex, in conjunction with XLF (Cernunnos).…”
Section: Introductionmentioning
confidence: 99%
“…There are at least five sites of DNA-PKcs autophosphorylation, the most frequent of which is T2609 (Chan et al, 2002;Douglas et al, 2002). CHO cells harboring DNA-PKcs with a T2609A mutation have radiosensitivity midway between normal and DNA-PKcs-deficient cells (Chan et al, 2002), suggesting that this autophosphorylation is functionally significant.…”
Section: End-joining Of Free Radical-mediated Double-strand Breaksmentioning
confidence: 99%